2018
DOI: 10.5863/1551-6776-23.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Significant Hyperbilirubinemia and Acute Hepatocellular Jaundice in a Pediatric Patient Receiving Deferasirox: A Case Report

Abstract: Despite a boxed warning, postmarketing reports of deferasirox-associated hepatic injury in patients with chronic transfusions are not well described. Hepatic impairment, including failure, has been reported to occur more frequently in patients older than 55 years and in those with significant comorbidities, including liver cirrhosis and multiorgan failure. In this case report, we describe significant hyperbilirubinemia and acute hepatocellular jaundice related to deferasirox in a 7-year-old female being treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Unlike previous findings, among the 13 pediatric patients, the levels of both direct bilirubin and unconjugated bilirubin were elevated (Table 2), which was the same as hepatocellular jaundice. [12] A direct/total bilirubin ratio of >15% to 20% or a DB level above 1.0 mg/dL is collectively defined as direct hyperbilirubinemia. [11] Twelve of the patients (92.3%) in our study were defined as direct hyperbilirubinemia according to the diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous findings, among the 13 pediatric patients, the levels of both direct bilirubin and unconjugated bilirubin were elevated (Table 2), which was the same as hepatocellular jaundice. [12] A direct/total bilirubin ratio of >15% to 20% or a DB level above 1.0 mg/dL is collectively defined as direct hyperbilirubinemia. [11] Twelve of the patients (92.3%) in our study were defined as direct hyperbilirubinemia according to the diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…With the wide and continuous consumption of DFS in clinical practice, adverse reactions caused by DFS exposure, i.e., gastrointestinal reactions, rashes, diarrhea, headache, fever, kidney injury, , and liver injury, , have been accumulating. DSF-consuming patients presented acute hepatitis accompanied with elevations of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities .…”
Section: Introductionmentioning
confidence: 99%
“…DFX long-term administration is known to be associated with various adverse events and mild to severe alterations of hepatic and kidney functions are the most relevant among them. Reports of drug-induced liver injury, including hepatic failure, have been reported during post-approval use of this compound, showing a hepatocellular pattern of injury with marked elevations in serum aminotransferase in the most severe cases 17 , 18 . A reversible, mild increase in serum creatinine (sCr) has been reported since the core registration trials 19 ; successively, acute nephrotoxicity related to DFX was reported in cases of proximal tubulopathy and Fanconi syndrome or acute interstitial nephritis.…”
Section: Introductionmentioning
confidence: 99%